THE ANTI- CANCER SYNERGISTIC EFFECT OF CHLOROQUINE ON CANCER CELLS PROLIFERATION (IN VITRO STUDY) (Academicia Globe: Inderscience Research, 2022)
This study aimed to investigate the possible in vitro cytotoxicity of Chloroquine .